Tandem electrocatalysis on Ag-modified copper cubes for carbon dioxide reduction: Dynamic interfacial phenomena and selectivity toward multicarbon products - Ruiz-Leon, D; Ruiz-Leon, D (ELSEVIER, 2026)
The electrochemical reduction of carbon dioxide (CO2) to multicarbon products remains a key challenge in sustainable energy conversion. We investigate how silver deposition time modulates the structure and performance of copper nanocubes (approximately 400 nm) for selective CO2 reduction. Silver was introduced via galvanic displacement to form bimetallic copper-silver tandem electrocatalysts. Structural and interfacial properties were correlated with catalytic behavior using in situ Raman spectroelectrochemistry, differential electrochemical mass spectrometry, and electrochemical impedance spectroscopy. Copper nanocubes modified with silver for 3 min exhibited enhanced selectivity toward ethylene and other multicarbon products, attributed to more efficient tandem catalysis and improved stabilization of carbon monoxide intermediates. In contrast, 2-minute samples adsorbed both CO and hydroxyl species, favoring single-carbon products and oxygenates such as acetone. In situ analyses revealed distinct interfacial dynamics and intermediate retention. These findings highlight the role of silver-induced surface tuning and the utility of a multi-technique approach for designing selective bimetallic electrocatalysts for CO2 conversion.